1986
DOI: 10.1002/pd.1970060308
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of a de novo complex chromosomal rearrangement involving four chromosomes

Abstract: A complex chromosome rearrangement, apparently a balanced translocation involving chromosomes 4, 6, 15 and 16, was found in cultured cells of amniotic fluid from a 32-year-old primigravida who requested amniocentesis for prenatal diagnosis because of a family history of mental retardation. Chromosome analysis of peripheral blood from both parents were normal. The couple was counselled for the prenatal diagnosis of this de novo complex translocation and, subsequently, elected to terminate the pregnancy. Post-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

1996
1996
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 17 publications
1
13
0
1
Order By: Relevance
“…Five pregnancies were terminated (Kim et al, 1986;Batista et al, 1993;Sikkema-Raddatz et al, 1995;Phelan et al, 1998;present case); two of them showed no apparent anomalies at autopsy (Batista et al, 1993;Sikkema-Raddatz et al, 1995). Six pregnancies were pursued.…”
Section: Discussionmentioning
confidence: 98%
“…Five pregnancies were terminated (Kim et al, 1986;Batista et al, 1993;Sikkema-Raddatz et al, 1995;Phelan et al, 1998;present case); two of them showed no apparent anomalies at autopsy (Batista et al, 1993;Sikkema-Raddatz et al, 1995). Six pregnancies were pursued.…”
Section: Discussionmentioning
confidence: 98%
“…2D). , 1995Sikkema-Raddatz et al, 1995Batista et al, 1993Kim et al, 1986Kohler et al, 1986Bogart et al, 19865;11) nosed balanced de novo CCR. The first was a CCR involving four chromosomes and seven breaks identified by CVS and later confirmed by amniocentesis.…”
Section: Discussionmentioning
confidence: 99%
“…Although prenatal ultrasound can detect many abnormalities, most CCRs are diagnosed postnatally and have non-specific signs with subtle dysmorphism that are not amenable to prenatal detection. Of the 11 previous reports of de novo balanced CCRs identified prenatally none involved mosaicism and only on two did ultrasound indicate a likely abnormal outcome when IUGR was detected prenatally (Kim et al, 1986;Cotter et al, 1996). Follow-up of the remaining cases postnatally revealed that three were dysmorphic with developmental delay (Ruiz et al, 1996;Bogart et al, 1986); one had speech delay (Stoll et al, 1979) but five were clinically normal (Kohler et al, 1986;Batista et al, 1993;Sikkema-Raddatz et al, 1995;Pruggmayer et al, 1990) (Table 1).…”
Section: Discussionmentioning
confidence: 89%